MASS CIRCUMCISION FOR UNPROSPEROUS CHILDREN: A COMMUNITY SERVICE MODEL BASED ON HEALTH AND SOCIAL VALUES - Mudatsir; Andhy Romdani; Daniel Bara Padang Allo; Andina Eka Mandasari; Adhitya Rahmat Taufiq; Aquinaldo Sistanto Putra; Revianti Coenraad; Muhammad Raka El Ghifari; Fahmi Rahmat Amanulloh (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
Access to safe and hygienic circumcision services remains a serious challenge for some Indonesians, especially for underprivileged families in densely populated urban areas like Bekasi. Ironically, circumcision has significant medical benefits, from preventing urinary tract infections and reducing the risk of sexually transmitted infections (STIs), to promoting reproductive hygiene. Beyond its medical benefits, circumcision also plays a strong social role as a symbol of a boy's transition to adulthood in Indonesian culture. This community service initiative aims to address the gap in access to circumcision services through a free mass circumcision program targeting children from underprivileged families. The implementation method includes target identification, health education for children and parents, circumcision using the dorsumsisi technique, and post-event support. The activity took place on July 12, 2025, in Bekasi, involving 40 children aged 5–13. Results showed that all participants underwent the circumcision process safely and without significant complications. This program not only positively impacted children's health and development but also strengthened self-confidence and strengthened social bonds within the community. This community service-based mass circumcision demonstrates that preventive health interventions can be integrated with social empowerment. This activity is worthy of widespread replication as a model of collaboration between higher education institutions, health workers, and local communities.